Carbon reduction effects of government digital attention - Hu, Rong; Song, Kaiyi (Frontiers in Environmental Science, 2025)
In the digital economy era, increasing government’s adoption and attention to digital technology is not only conducive to accelerating the improvement of governance capacity, but also an important measure to achieve green economic development. This paper uses text analysis to measure the government digital attention at the city level, and then uses panel data econometric models to estimate the impact of government digital attention on carbon emissions reduction. The findings reveal that government digital attention can significantly reduce carbon dioxide emissions by improving the government’s low-carbon governance, strengthening the public’s low-carbon attention, and encouraging the enterprises’ low-carbon transformation. Further, government digital attention mainly reduces carbon dioxide from direct energy consumption, transportation and electricity product. The carbon reduction effect of government digital attention is also affected by degree of marketization, and the high degree of marketization helps to reinforce the effect. Moreover, there is spatial heterogeneity in the effect, it is more significant in the eastern region. Our conclusions are then of important implications for promoting China’s carbon dioxide reduction and achieving high-quality sustainable development.